(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the effectiveness of the Central Bank of Uzbekistan (CBU) anti-crisis monetary policy during the 2020–2023 polycrisis period, characterised by the simultaneous impact of the COVID-19 pandemic, the geopolitical and economic repercussions of the Russia-Ukraine conflict, and the global inflationary surge. Drawing on macroeconomic time-series data from the CBU, the IMF, the World Bank, and the Bank for International Settlements, the study employs a multi-method research design combining serial case study analysis, interrupted time series (ITS) assessment, and a three-country comparative reference framework (Uzbekistan, Kazakhstan, Georgia). The findings reveal that the CBU achieved short-run macroeconomic stabilisation across all three shock episodes—maintaining positive GDP growth, preserving banking system solvency, and containing excessive exchange rate depreciation. However, three systemic weaknesses were identified: the absence of a sectoral monitoring mechanism within targeted refinancing operations; the reactive character of foreign exchange market interventions; and underdevelopment of the communication infrastructure required for effective inflation expectations management. The paper concludes with five evidence-based institutional recommendations calibrated to Uzbekistan’s structural context and the specific demands of polycrisis monetary management.